Advances in Non Destructive Evaluation Proceedings of NDE 2020 - Mandayam, Shyamsunder; Sagar, Sarmishtha Palit; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the proceedings of the Conference and Exhibition on Non Destructive Evaluation (NDE 2020). The contents of the volume encompass a vast spectrum from Conventional to Advanced NDE including novel methods, instrumentation, sensors, procedures, and data analytics as applied to all industry segments for quality control, periodic maintenance, life estimation, structural integrity and related areas. This book will be a useful reference for students, researchers and practitioners.
Evaluation of Parallel Processing Employed in Industrial Computed Tomography -- Towards Rapid, In-situ Monitoring of Thermal Barrier Coating Degradation Using Eddy Current Technique -- Eddy Current Thermography as a Tool for Detecting the Location and Dimension of Edge Defects in CrMo Steel Plate -- Indian Make Portable and Real-time Shearography System (IMPRESS) for Non-Destructive Testing (NDT) -- Real-time Detection of Defects on a Honeycomb Composite Sandwich Structure using Digital Image Correlation (DIC) -- Novel Data Processing Approaches for Testing and Evaluation of Mild Steel Sample using Frequency Modulated Thermal Wave Imaging -- Barker Coded Thermal Wave Imaging for Testing and Evaluation of Mild Steel -- Proximity: An Automatic Approach for Defect Detection and Depth Estimation in Infrared Non-Destructive Testing -- A Comparative Evaluation of Two Scanning Modalities in Industrial Cone Beam Computed Tomography -- Subsurface Defect Detection in Conducting Materials Through Transient Eddy Current NDE and Apparent Conductivity Calculations.
Keywords: Industrial engineering; Production engineering; Measurement; Measuring instruments; Mechanics, Applied; Solids; Mathematical physics; Materials -- Analysis; Industrial and Production Engineering; Measurement Science and Instrumentation; Solid Mechanics; Theoretical, Mathematical and Computational Physics; Materials Characterization Technique; Nondestructive testing -- Congresses